Multipurpose watermarking realizing image copyright notification,copyright protection and content authentication - ZHU Cong-xu (Tongxin xuebao)
A multipurpose image watermarking scheme based on chaotic systems and sub-image lifting wavelet transformation（LWT） was proposed.Firstly, the host image was divided into 8×8 sub-images and each sub-image was performed 2-level LWT.Then, the invisible watermarks for copyright protection and content authentication were respectively embedded into low and intermediate frequency LWT components of some sub-images that were randomly selected by general Arnold map.A new kind of quantization technique was adopted in the embedding process and the extracting process was blind.Secondly, the visible watermarks for copyright notification were embedded into the image spatial domain based on image fusion method, in which the embedding coefficients were generated by the 4D hyperchaotic sequences.Experimental results were presented, showing that the proposed watermarking scheme is effective.